THE PRAGMATIC ROLE OF INTERTEXTUAL REFERENCES IN SCIENCE MAGAZINE NARRATIVES - Shahnozabegim Yoqubjonova; Nodirabegim Yoqubjonova (Research Focus International Scientific Journal, 2026)
This study investigates the pragmatic functions of intertextual references within the narratives of popular science magazines. As science communication seeks to bridge the gap between specialized knowledge and public understanding, authors frequently utilize intertextuality to establish authority, simplify complex concepts, and engage the reader’s cultural background. Using a corpus of articles from prominent science publications, this research analyzes how references to previous scientific works, cultural icons, and historical events are strategically embedded. The findings reveal that intertextuality serves three primary pragmatic roles: cognitive scaffolding, social alignment, and rhetorical persuasion. The study concludes that intertextual references are essential tools for constructing narrative coherence in science journalism, transforming esoteric data into culturally accessible knowledge.